Nutritional Regulation of Gene Expression: Carbohydrate-, Fat- and Amino Acid-Dependent Modulation of Transcriptional Activity - Haro, Diego (Int J Mol Sci, 2019)
The ability to detect changes in nutrient levels and generate an adequate response to these changes is essential for the proper functioning of living organisms. Adaptation to the high degree of variability in nutrient intake requires precise control of metabolic pathways. Mammals have developed different mechanisms to detect the abundance of nutrients such as sugars, lipids and amino acids and provide an integrated response. These mechanisms include the control of gene expression (from transcription to translation). This review reports the main molecular mechanisms that connect nutrients’ levels, gene expression and metabolism in health. The manuscript is focused on sugars’ signaling through the carbohydrate-responsive element binding protein (ChREBP), the role of peroxisome proliferator-activated receptors (PPARs) in the response to fat and GCN2/activating transcription factor 4 (ATF4) and mTORC1 pathways that sense amino acid concentrations. Frequently, alterations in these pathways underlie the onset of several metabolic pathologies such as obesity, insulin resistance, type 2 diabetes, cardiovascular diseases or cancer. In this context, the complete understanding of these mechanisms may improve our knowledge of metabolic diseases and may offer new therapeutic approaches based on nutritional interventions and individual genetic makeup.